The maximum use of alfalfa meal in protein supplement mixtures for fattening fall pigs in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment was designed .to secure information on maximum use of alfalfa meal in protein supplemental mixtures for pigs in dry lot. The experiment on next page reports similar information from pigs on alfalfa pasture. In this 1954-55 test four lots of fall-farrowed pigs were self-fed corn in dry lot. Each lot received different amounts of alfalfa meal in protein supplements. Lot 1 received an animal plant protein mixed supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. ,Lot 2 received one of 4 parts tankage, 4 parts ,soybean meal, and 2 parts alfalfa meal. Lot 3 received one of 4 parts tankage, 4 parts soybean meal, and 3 parts alfalfa meal; and Lot 4 received one of equal parts tankage and alfalfa meal.
Keywords: Swine; Alfalfa meal; Protein; Gain